Інструменти штучного інтелекту для створення контенту веб-ресурсів - Хрустальов, Є. К. (ХНУРЕ, 2024)
The work examines the possibility of using artificial intelligence algorithms in creating and analyzing content on web platforms. Machine learning methods and natural language processing technologies are discussed, which can improve the quality of content, personalize it to the needs of the audience, and ensure the safety of the online environment. The advantages and problems of using artificial intelligence algorithms in content marketing and information management on web resources are considered.
Keywords: створення контенту веб-ресурсів; content on web platforms